Synthesis, Antitumor Activity, and Structure-activity Relationship of Some Benzo[a]pyrano[2,3-c]phenazine Derivatives - Gao, Jing; Chen, Ming; Tong, Xue; Zhu, He; Yan, Hongbin; Liu, Daichun; Li, Wanjing; Qi, Shengyu; Xiao, Dake; Wang, Yongzhi; Lu, Yuanyuan; Jiang, Feng (Combinatorial Chemistry & High Throughput Screening, 2015)
A series of benzo[a]pyrano[2,3-c]phenazine derivatives with a wide range of substitutions at ring C of the benzophenazine were designed and synthesized using the one-pot, four-component domino reactions. The targeted compounds were evaluated for their antitumor activities against HCT116, MCF7, HepG2 and A549 cancer cell lines in vitro. The most active compound 61,2,1,9 featured the CN and p-dimethylamino phenyl substituents on γ-pyran structure on ring C. Significantly, compound 61,2,1,9 was found to have the highest growth inhibitory activity against the HepG2 cell line with IC50 values of 6.71 µM, which was 1.6-fold more potent than positive control anticancer drug Hydroxycamptothecine (HCPT). Furthermore, structure-activity relationship (SAR) studies on the substitutions at ring C were discussed in details.
Keywords: SAR